LOKALITAS ISLAM PESISIR (Studi Kasus Aktifitas Perembus dalam Perspektif ‘Urf ‘Izzuddin bin ‘Abd al-Salam Di Desa Kaduara Barat Pamekasan Madura) - Mansur Mansur (LP2M IAI Miftahul Ulum Pamekasan, 2019)
Perembus activities have many roles. Starting from serving financial and capital services, fishing partners and companies, agents of socio-economic change, culture-religious and education. There is a unique triangle of relations between the perembus-jhereghen jurung in selling fish catches and the perembus-relationship relation with the provision of facilities and fees, which all have the interest to make large financial gains and seem to shift Islamic values. With a qualitative-ethnographic approach, this study will give birth to a new type of religion in the context of Islam in coastal Madura. Perembus as a company 'intermediary' with fishermen provides a strategic role whose position is parallel even above the social status of the clerics and religious teachers. For the coastal community, the perembus is orèng soghi, 'ruler' and a place to complain for oreng miskèn. Perembus activities in the local coastal ‘urf do not rely on cultural fields, sacred tombs, sacred wells and sacred mosques with the aim of